Dynamic Analysis on Stainless Steel New Generation Passenger Coach using Multibody Dynamic System - Agus Susanto; Saka Marga Redi; Bi Asngali; Michael Martin; Ridho Muarief (Manutech : Jurnal Teknologi Manufaktur, 2022)
Stainless-steel passenger coaches are the most operated passenger trains in Indonesia, which are manufactured by the Indonesian railway industry, (PT. INKA), from its first launch to the last generation of trains. PT. INKA still keeps innovating to improve the performance of these trains. Nowadays, this passenger coach is being developed to reach a speed of more than 120 km/hour, while keeping the stability, ride quality index, and ride comfort index during operation. This new train would be called a stainless-steel new generation (SS-NG) passenger coach. To reach the target, one of the methods is redesigning the old bogie structure of the stainless-steel passenger coach. The purpose of this research is to design a new bogie for the SS-NG passenger coach and analyze its dynamics during operation at high-speed using multibody simulation. The result was then compared to the existing passenger coach (SS-2018) which was structured by the old bogie one. Sperling’s method was utilized for evaluating the ride comfort index of all designed trains. As a result, the SS-NG with a new bogie design showed stable operation and gave an acceptable ride comfort index based on Sperling’s method even though travels at 240 Km/h in speed. The results will be important for improving the performance of any train, especially the SS-NG passenger coach which will be fabricated by PT. INKA.